Exploring the Role of Religious Media in Shaping Public Perceptions Towards Climate Change in Egypt - Ashour, Hebatullah Ashour Abdel Fatah Ibrahim (AUC Knowledge Fountain, 2025)
Climate change poses significant threats globally, with particular vulnerability noted in developing nations like Egypt. While effective communication is crucial for societal engagement, the role of influential actors like religious media within specific cultural contexts remains under-explored. This thesis investigates the role and communication practices of religious media (Islamic and Coptic Christian) concerning climate change in Egypt, a country where religious institutions command significant public trust and influence. Existing literature highlights gaps in understanding how these specific media outlets navigate and frame climate change discourse. Employing Framing Theory and Communication for Development (DevCom) Theory as a combined framework, this study aims to evaluate how Egyptian religious media practitioners perceive their role, construct messages, and engage audiences regarding climate change. The research utilized a qualitative methodology, conducting in-depth interviews with practitioners from various religious media platforms (newspapers, radio, television, social media). The findings reveal that practitioners perceive a strong responsibility to address climate change, rooted in religious teachings and societal trust. They navigate the intersection of faith and science by drawing authority from sacred texts, invoking core theological concepts like stewardship, integrating scientific expertise, and contextualizing messages for daily life. Key communication strategies identified include emphasizing simplicity and relevance, leveraging trusted religious figures, customizing content for diverse audiences, and focusing on actionable solutions. However, significant challenges persist, including audience apathy, competition with socioeconomic priorities, the misconception of individual inefficacy, resource limitations, and navigating the complex media and political landscape. While collaborations exist, particularly with governmental and academic bodies, practitioners highlight a need for more strategic partnerships with environmental organizations. This study contributes empirical insights into the unique dynamics of climate change communication by religious media in Egypt. It underscores the potential of leveraging faith-based frameworks for environmental engagement while also highlighting the practical and structural barriers faced by practitioners. The findings offer valuable implications for developing culturally resonant communication strategies and fostering more effective collaborations to address the climate crisis in Egypt and potentially similar contexts. Keywords: Climate Change Communication, Religious Media, Egypt, Framing Theory, Communication for Development, Environmental Communication, Islam, Coptic Christianity, Media Practitioners